2023
DOI: 10.1037/aca0000623
|View full text |Cite
|
Sign up to set email alerts
|

The role of imagery and emotion in the aesthetic appeal of music, poetry, and paintings.

Kendra Mehl,
Maria Gugliano,
Amy M. Belfi

Abstract: A ubiquitous aspect of the human experience is the creation of and engagement with art. While the field of empirical aesthetics has traditionally focused on visual stimuli, researchers have more recently begun investigating the experience of many different artistic domains, such as architecture, dance, and poetry. However, most prior work has investigated a single artistic domain, rather than comparing across different categories of art. To better understand how aesthetic experiences may be similar (or differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Other relevant work has found that subjective perceptions of a poem’s style, such as whether the poem is perceived to have rhythm and can be read fluently, are important predictors of its aesthetic appeal (Ludtke et al, 2014). More recently, we identified that vividness of visual imagery was an even more important predictor for poetry than for other aesthetic stimuli, that is, visual arts and music (Mehl et al, 2023).…”
mentioning
confidence: 99%
“…Other relevant work has found that subjective perceptions of a poem’s style, such as whether the poem is perceived to have rhythm and can be read fluently, are important predictors of its aesthetic appeal (Ludtke et al, 2014). More recently, we identified that vividness of visual imagery was an even more important predictor for poetry than for other aesthetic stimuli, that is, visual arts and music (Mehl et al, 2023).…”
mentioning
confidence: 99%